EXAMINING SPEECH ACTS AND PRAGMATIC IMPLICATIONS IN BBC NEWS HEADLINES: MEDIA DISCOURSE ANALYSIS ON THE PALESTINE-ISRAEL CONFLICT - Muslim, Ahmad Bukhori; Hidayoza, Prima (Universitas PGRI Sumatera Barat, 2024)
The framework underpinning the Speech Acts theory developed by Searle (1979) examining the headlines of one online International news advocating the never-ending conflict of Palestine-Israel becomes a fundamental analysis of this research. The qualitative case study is presented by 26 selected headlines (ranging from 6 to 13 words) from BBC News distinguished with the world–Middle East section of the Gaza and Israel war. This covers the headline from October 2023 to January 2024. The document analysis through the written texts of headlines was the main data. The research shows that there are four of five categories of speech acts found in this research, calculating “assertive” and “commisive” as both the largest and the least frequent models under the main framework of the Searle model. The pragmatics analysis is also integrated which presents five different types of implications including the involvement of external actors, statistics of released hostages, casualties of the war, Benjamin Netanyahu's point of view, and the war condition.